2009
DOI: 10.1080/13554790802709054
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced speech perception capabilities in a blind listener are associated with activation of fusiform gyrus and primary visual cortex

Abstract: Blind individuals may learn to understand ultra-fast synthetic speech at a rate of up to about 25 syllables per second (syl)/s, an accomplishment by far exceeding the maximum performance level of normal-sighted listeners (8-10 syl/s). The present study indicates that this exceptional skill engages distinct regions of the central-visual system. Hemodynamic brain activation during listening to moderately- (8 syl/s) and ultra-fast speech (16 syl/s) was measured in a blind individual and six normal-sighted control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 21 publications
4
30
0
2
Order By: Relevance
“…The test materials of this investigation – a subset of the stimulus corpus of the preceding single-case study [19] – encompassed 40 different text passages (sentences) obtained from newspapers and transformed into acoustic speech signals by means of a formant synthesizer (text-to-speech system) at the Institute of Phonetics of the Saarland University (screen reader software JAWS 2008; male voice; http://www.freedomsci.de). All utterances were first recorded at a normal speaking rate, amounting to 4–6 syl/s.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The test materials of this investigation – a subset of the stimulus corpus of the preceding single-case study [19] – encompassed 40 different text passages (sentences) obtained from newspapers and transformed into acoustic speech signals by means of a formant synthesizer (text-to-speech system) at the Institute of Phonetics of the Saarland University (screen reader software JAWS 2008; male voice; http://www.freedomsci.de). All utterances were first recorded at a normal speaking rate, amounting to 4–6 syl/s.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, patients suffering from vision impairments may considerably benefit, e.g., during academic education, from screen-reading text-to-speech systems, operating at ultra-fast syllable rates [18]. Using functional magnetic resonance imaging (fMRI), a preceding single-case study of our group first documented significant hemodynamic activation of right-hemispheric primary visual cortex (V1) and contralateral fusiform gyrus (FG) in a blind university student with high ultra-fast speech perception capabilities during application of compressed verbal utterances (16 syl/s) whereas, by contrast, similar responses did not emerge in a series of sighted control subjects [19]. …”
Section: Introductionmentioning
confidence: 99%
“…There was improved speech perception ability in visual impaired participants with natural as well as synthetic ultra-fast speech. For ultra-fast speech, significant activation was seen in occipital cortex and left fusiform gyrus for visual impaired participants 21 . Hence the congenital visual impairment have superior speech perception in noise due to better frequency and temporal resolution.…”
Section: Discussionmentioning
confidence: 99%
“…While blind people do not have the ability to see the world through their sense of sight, they often develop better verbal memory or better hearing than sighted people. Connected to this, a group of neuroscientists recently reported that blind people can understand spoken language at a rate up to about 22 syllables per second compared to normal-sighted listeners who can comprehend up to 8-10 syllables per second (Hertrich, Dietrich, Moos, Trouvain, & Ackermann, 2009). 56 The study mentioned that this occurs because the brain region sighted people would normally use to respond to visual stimulation is used by blind people to respond to speech.…”
Section: Ableism: Towards An Ability Divide?mentioning
confidence: 97%
“…This is an example of how the brain rewires itself in such a way that it compensates for lost senses, and in some cases develops abilities out of what we normally expect in 'normal' individuals. However, there are many factors (such as age) that influence the brain's rewiring capabilities (Hertrich et al, 2009).…”
Section: Ableism: Towards An Ability Divide?mentioning
confidence: 99%